Association of Peripheral Artery Disease with Obesity: Impact of Obesity on Peripheral Artery Disease - Zakir, Humaira; Aman, Habiba; Khokhar, Amanullah; Irfan, Saboohi; Memon, Nazeer Ahmed; Almas, Tabassum (Pakistan Journal of Health Sciences, 2024)
Obesity has emerged as a significant contributor to the development and progression of Peripheral Artery Disease (PAD) which has significant impact on local population as the frequency of obesity is high. Objective: To determine the association between obesity and the development of Peripheral Artery Disease in patients attending General Medicine clinics. Methods: This cross-sectional study using non-probability convenient sampling was done to investigate association of obesity on the development of peripheral artery disease for six months. The study population consisted of adult patients (aged 18 and above) attending cardiovascular and metabolic clinics at Al-Tibri Medical Hospital. Inclusion criteria included patients with PAD confirmed by ankle-brachial index (ABI) of less than 0.90 into mild, moderate and severe. Patients with acute infections, malignancies were excluded. Hypothesis of the study stated that whether there was an association between obesity and development of PAD or not. Statistical analysis done using SPSS version 23.0, involved association between BMI and PAD using chi-square tests keeping p<0.05 statistically significant. Results: The mean age of participants was 50.87 ± 8.32 years. Mean ABI was 1.02 ± 0.12. Individuals having normal BMI (18-22.99 kg/m²), 6 had PAD. In the overweight category (23-24.99 kg/m²), 8 had PAD. In the Obese I category (25-26.99 kg/m²), 11 had PAD. In the Obese II category (27-29.99 kg/m²), 20 had PAD. In the Obese III category (>30 kg/m²), 24 had PAD. A significant association between BMI and PAD was observed between both groups (p-0.01). Conclusion: A significant association between obesity and PAD development was observed in this study. Obesity was a significant factor in the development of PAD. The significant association between obesity and PAD observed in this study underscores the need for public health interventions aimed at weight management